A study on mother‐to‐fetus/infant transmission of influenza A(H7N9) virus: Two case reports and a review of literature - Wang, Jiajia; Xu, Hua; Mu, Chuanyong; Chen, Cheng; Guo, Lingchuan; Chen, Liling; Huang, Jian‐an; Guo, Qiang (The clinical respiratory journal, 2018)
Objectives The prevention strategies for mother‐to‐fetus/infant transmission of H7N9 virus have not been well understood, and the study on this subject will provide further insights. Methods Reverse transcriptase polymerase chain reaction assay was undertaken to detect H7N9 virus in samples from a pregnant women, a postpartum woman, and their fetus/infant. Pathological features of tissues from the dead fetus were evaluated with hematoxylin and eosin staining. Hemagglutination inhibition assay was used to detect virus‐specific antibodies. Furthermore, relevant literatures were reviewed and analyzed. Results A 28‐year‐old pregnant woman was hospitalized for H7N9 infection and prescribed with oseltamivir and peramivir for 2 days before admission. The fetal heart beating stopped on day 4, the dead fetus was delivered on day 13, and the woman expired on day 26. All fetal tissues were H7N9 virus‐negative. A 28‐year‐old woman delivered a newborn on December 20, 2016. Five days later, she developed influenza‐like symptoms and was confirmed with H7N9 infection. She had close contact with her infant for 9 days. Oseltamivir and peramivir were prescribed within 2 days after illness onset. A throat swab and a pair of serum samples from the infant were all negative for H7N9 virus during 4‐week follow‐up. In total, ten studies referring to transplacental transmission and four reports on maternal infection of H7N9 virus were reviewed and analyzed. Conclusion No evidence showed H7N9 virus infection in both fetus and infant. The early administration of neuraminidase inhibitor seemed beneficial in preventing mother‐to‐fetus/infant transmission of H7N9 virus.